P551 6-Thioguanine nucleotide levels are associated with mucosal healing in patients with Crohn's disease: A multi-centre, international study. (16th January 2018) - Mao, R; Guo, J; Luber, R; Chen, B -l; He, Y; Zeng, Z -r; Ben-Horin, S; Sparrow, M; Xavier, R; Chen, M -h
Abstract: Background: The level of 6-thioguanine nucleotides (6-TGN) has been reported to be associated with clinical remission in patients with Crohn's disease (CD) receiving maintenance treatment with thiopurines. Whether 6-TGN levels are associated with mucosal healing (MH) has seldom been investigated. We aimed to assess the correlation between 6-TGN levels and MH in patients with CD. Methods: This was a retrospective cross-sectional observational multi-centre study of 119 patients with CD treated with thiopurines in three IBD referral centres (France, Australia and China) between June 2012 and April 2016. Established CD patients who underwent ileocolonoscopy during thiopurine treatment were included. MH was defined as simple endoscopic score-CD <3. Univariate and multivariable regression analyses were used to evaluate variables associated with MH. Results: The mean concentration of 6-TGN in MH group was higher compared with that in non-MH group (359.0 ± 226.7 pmol/8 × 10 8 RBC vs. 277.1 ± 170.5 pmol/8 × 10 8 RBC) ( p = 0.017). The cut-off 6-TGN concentration of 397.3 pmol/8x108RBC was 86.7% specific for MH, with a sensitivity of 35.3% and area under curve (AUC) of 0.631 ( p = 0.010). On multivariate analysis, 6-TGN levels were associated with MH (odds ratio [OR] 3.287, 95% confidence interval [CI] 1.348–8.017; p = 0.009) while late initiation of AZA (longer duration from disease onset) was inversely associated with MH (OR 0.972, 95% CI 0.954–0.991; p = 0.004). Conclusions: Higher 6-TGN levels are independently associated with a reduced rate of endoscopically active disease and a higher rate of mucosal healing in CD patients. Prospective studies of adequate sample size are required to confirm these findings.